A novel ostracod record from Lake Simcoe (Canada) tracks inputs of glacial meltwater, relative temperature changes, and sources of inorganic carbon throughout the last ~14 000 years - Doyle, R.M.; Bumstead, N.; Lewis, C.F.M.; Longstaffe, F.J. (Zenodo, 2022)
A new ostracod record from Lake Simcoe (Ontario, Canada) sheds light on interactions between the earth, atmosphere and cryosphere in southern Ontario during the late Pleistocene and Holocene. Proxies employed in this study include (i) oxygen and carbon isotope compositions of ostracod valves ( δ 13 C valve and δ 18 O valve , respectively), (ii) ostracod assemblages, and (iii) physical properties of the sediment. Estimates of the oxygen isotope composition of lake water ( δ 18 O lake water ), derived from measurements of δ 18 O valve , are paired with a well-constrained sediment chronology to uncover the history of glacial meltwater inputs to Lake Simcoe. Glacial Lake Algonquin, which spawned from the gradual melting of the Laurentide Ice Sheet (LIS), inundated Lake Simcoe from the beginning of the record (~14 000 cal BP) until ~12 050 cal BP. An additional pulse of glacial meltwater likely occurred ~11 000 cal BP when Early Lake Mattawa overflowed into the Lake Simcoe basin. From ~11 000 cal BP to present, variations in δ 18 O lake water closely match those of previously published pollen-based temperature reconstructions from the same sediment core. Ostracod assemblages also reflect these temperature variations, highlighting the influence of air temperatures on in-lake conditions. Estimates of the carbon isotope composition of dissolved inorganic carbon ( δ 13 C DIC ), derived from measurements of δ 13 C valve , reveal that the stable carbon-isotope systematics of DIC in Lake Simcoe were mostly controlled by bedrock and detrital carbonate dissolution rather than production/respiration or lake level. Physical properties of the lake sediment, such as grain size, magnetic susceptibility, sediment accumulation rate and sediment mineralogy substantiate the above findings. A pronounced increase in accumulation rate, and subtler increases in grain size and detrital carbonate contents between ~8300 and 8000 cal BP, may reflect an abrupt transition from cold/dry to wet/warm conditions resulting from the collapse of the ...